Post-phototherapy neonatal bilirubin rebound: a potential cause of significant hyperbilirubinaemia. Issue 1 (13th October 2005) - Kaplan, M; Kaplan, E; Hammerman, C; Algur, N; Bromiker, R; Schimmel, M S; Eidelman, A I
Abstract : Aim: To determine the incidence of post-phototherapy neonatal plasma total bilirubin (PTB) rebound. Methods: A prospective clinical survey was performed on 226 term and near-term neonates treated with phototherapy in the well baby nursery of the Shaare Zedek Medical Center from January 2001 to September 2002. Neonates were tested for PTB 24 hours (between 12 and 36 hours) after discontinuation of phototherapy, with additional testing as clinically indicated. The main outcome measure, significant bilirubin rebound, was defined as a post-phototherapy PTB ⩾256 μmol/l. Phototherapy was not reinstituted in all cases of rebound, but rather according to clinical indications. Results: A total of 30 (13.3%) neonates developed significant rebound (mean (SD) PTB 287 (27) μmol/l, upper range 351 μmol/l). Twenty two of these (73%) were retreated with phototherapy at mean PTB 296 (29) μmol/l. Multiple logistic regression analysis showed significant risk for aetiological risk factors including positive direct Coombs test (odds ratio 2.44, 95% CI 1.25 to 4.74) and gestational age <37 weeks (odds ratio 3.21, 95% CI 1.29 to 7.96). A greater number of neonates rebounded among those in whom phototherapy was commenced ⩽72 hours (26/152, 17%) compared with >72 hours (4/74, 5.4%) (odds ratio 3.61, 95% CI 1.21 to 10.77). Conclusion: Post-phototherapy neonatal bilirubin rebound to clinically significant levels may occur, especially in cases of prematurity, direct Coombs test positivity, and those treated ⩽72 hours. These risk factors should be taken into account when planning post-phototherapy follow up.